Agricultural information networks of farm women and role of agricultural extension: the case of Dale Woreda, Southern Nations, Nationalities & Peoples’ Region - Kaske, D.K. (Haramaya University, 2007)
Ethiopian rural women make significant contribution to agriculture and are the mainstay of the farm labor. They work in all aspects of agriculture. In addition to their active engagement in agriculture, women are responsible for all household chores. Despite their immense contribution to the agriculture, rural women often face difficulties than men in gaining access to agricultural information. The Ethiopian agricultural extension system suffers from a number of weaknesses in its services for rural women. There is, therefore, an alarming need to improve agricultural extension work with the rural women. Therefore, this study is intended to analyze the agricultural information network of farm women; to identify factors influencing farm women’s information network output and to identify the constraints and opportunities of extension services in reaching out to women in Dale Woreda, Sidama Zone, SNNPR. Three stages sampling were used in which both non-random sampling and random sampling procedures was followed to select four Peasant Associations and 160 respondents. Structured interview schedule was used for collecting the essential quantitative data from the sampled respondents. To generate qualitative data, field observations; informal interview with key informants; discussion with separate focus groups of women and men farmers were conducted. The quantitative data were analyzed using descriptive statistical tools and also χ2 = test, Cramer’s V, Pearson’s Correlation coefficient & Multiple Linear Regression were employed. The result of the study shows that, neighbors or friends are the major and the most important source of information for the farm women. The major output of the study indicates that knowledge of dairy farming practice of women farmers was significantly influenced by communication skill, interpersonal trust, social participation, total annual income, extension participation, empathy of respondents and access to credit. The major constraints identified in agricultural information network of farm women were low participation of women in extension programs; poor access to credit; absence of market information and alternative market for products; extension methods contribute less as source of information. Therefore, it is recommended that, the extension system operating in the area, need to be strengthened further to increase the flow of information to women for rural transformation.